Patterns of Remating Behaviour in Ceratitis (Diptera: Tephritidae) Species of Varying Lifespan - Pogue, Tania; Malod, Kevin; Weldon, Christopher W. (Frontiers in Physiology, 2022)
Trade-offs between life-history traits offset the energetic costs of maintaining fitness in complex environments. Ceratitis species have been recorded to have long lifespans, which may have evolved in response to seasonal resource fluctuation. It is thus likely that reproductive patterns have evolved concomitantly as part of the trade-off between lifespan and reproduction. In this study we investigated how reproductive patterns differ between Ceratitis cosyra (Walker) and Ceratitis capitata (Wiedemann) (Diptera: Tephritidae), two species with different average and maximum lifespans. Females of both species were mated and patterns of female survival, fecundity, remating and sperm storage were tested. Ceratitis cosyra had a higher rate of survival and a lower fecundity when compared with the shorter-lived C. capitata, suggesting that both species exhibit a trade-off between lifespan and reproduction. Both species showed a similar and consistent willingness to remate, despite declines in sperm storage, suggesting that sperm alone does not fully inhibit remating. As expected, C. cosyra transferred high numbers of sperm during the first mating. However, sperm stores declined unexpectedly by 14 days. This indicates that males might transfer large ejaculates as a nuptial gift, that female then later degrades as a source of nutrients. Large declines in sperm storage may also indicate that females discard excess sperm stores due to the toxicity involved with storing sperm. These results do not suggest that patterns of sperm storage and remating align with lifespan and resource seasonality in these species, but a wider range of species needs to be assessed to better understand variation in Ceratitis mating systems.